المعزولة من اصابات سريرية مختلفة لبعض المضادات الحيوية Pseudomonas aeruginosa مقاومة جرثومة - مهدي عريبيسناء (University of Thi-Qar Journal of Science, 2019)
This study was conducted for the isolation and identification of P.aeruginosa from different clinical cases. The total number of samples were 129 sample wounds; burns; urinary tract ; chronic otitis media infections and were collected from and detection of their susceptibility for 15 antibiotic . The total number of isolated and confirmed P.aeruginosa were 38 out from 129 samples. The distribution of positive isolates were 12 from 38 cases otisit infections ; 8 from 19 samples of burnes ; 10 from 50 samples of urin ;8 from 22 samples of wounds .All isolates show A high perecentage of resistance (100%) aginst penicillin and ampicillin .the lower resistance was registrated aginst Amikacin (30%), azthromycin (22%) ;ciprofloxacin (18%). According to the results our isolates were in consistent with what is called Multi Drug Resistant P.aeruginosa ( MDRPA) .The results of this study show that sex ;age and proloned antimicrobial admistration were fundamental factoers in reasing the chance of infection .